Consumer trust in organic milk of different brands: the role of Chinese organic label. Issue 7 (4th July 2016) - Yin, Shijiu; Chen, Mo; Chen, Yusheng; Xu, Yingjun; Zou, Zongsen; Wang, Yiqin
Abstract : Purpose: Purpose – Organic certification system became important means to restore consumer confidence in China. The study focused on consumer trust in organic milk of different brands and its influencing factors. Design/methodology/approach: Design/methodology/approach – The data were collected from 876 randomly selected consumers in Shandong province, China. And an ordered logistic model was established to analyze influencing factors of consumer trust. Findings: Findings – Chinese consumers generally lack trust in organic milk. Consumer trust for different brands of organic milk was different, and was not high in general. Various factors, namely, age, education years, food safety awareness, evaluation of government regulation policy, evaluation of organic milk price, and purchase convenience, have a significant impact on consumer trust. Factors, such as income, environmental protection consciousness, and risk consciousness, are not significant. Originality/value: Originality/value – This research is of academic value and of value to policy makers and suppliers. Government should promote institutional arrangement and strengthening supervision in production, certification, and circulation of organic products. Organic suppliers should implement reliable marketing strategy, such as correct pricing, and build a more extensive and convenient distribution network.